Energy and exergy analysis of Ca(OH)2/CaO dehydration-hydration chemical heat pump system: Effect of reaction temperature. (July 2021) - Gupta, Aman; Armatis, Paul D.; Sabharwall, Piyush; Fronk, Brian M.; Utgikar, Vivek
Highlights: Experimental investigations on multiple scales on a thermochemical energy storage system. Effect of reaction temperature on conversion in reversible dehydration-hydration reaction couple. Energy and exergy efficiency analysis of the system and identification of potential solution for increasing the efficiencies. Effect of reaction cycles on the structure of the solid reactant. Abstract: Thermochemical energy storage (TCES) is based on the principle of employing a reversible chemical reaction for thermal energy storage. TCES is characterized by high energy density and low parasitic heat loss while also offering potential functionality as a chemical heat pump (CHP) to boost temperature. Results of experiments conducted on a Ca(OH)2 /CaO TCES system based on reversible dehydration-hydration reactions are reported in this paper. Dehydration of Ca(OH)2 pellets conducted in a thermogravimetric-differential calorimetry analyzer (TGA-DSC) revealed that the optimum heating rate ranges from 10-15 K/min for the decomposition of Ca(OH)2 . Repeated dehydration-hydration cycles were conducted in a bench scale reactor system under various reaction conditions. It was found that the temperature rise during hydration reaction was dependent on the extent of conversion during the dehydration process. The energy and exergy efficiencies of the dehydration-hydration cycles were found to range from 76% to 79% and 85% to 91%, respectively. Visual and scanning electron microscopic examinations of the product after each reaction revealed structural changes and formation of cracks in the pellets. These changes did not affect the thermal efficiency of the process. Results of this study provide a foundation for the development of Ca(OH)2 /CaO CHPs for large-scale thermal energy storage systems.